2022
DOI: 10.1007/s11104-022-05302-x
|View full text |Cite
|
Sign up to set email alerts
|

Soil aggregate stability of forest islands and adjacent ecosystems in West Africa

Abstract: This publication is made publicly available in the institutional repository of Wageningen University and Research, under the terms of article 25fa of the Dutch Copyright Act, also known as the Amendment Taverne. This has been done with explicit consent by the author.Article 25fa states that the author of a short scientific work funded either wholly or partially by Dutch public funds is entitled to make that work publicly available for no consideration following a reasonable period of time after the work was fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 74 publications
0
9
0
Order By: Relevance
“…Besides contributing to increased SOC, maize roots are also known to produce exudates, which instantaneously bind soil aggregates (Six et al, 2004); thus, maize and legume systems in rotation as in CMr, enhanced macroaggregate stability more than cowpea monoculture (Tables 4 and 5). Some studies reported association of macroaggregates with soil organic carbon content (Six et al, 2000;Curaqueo et al, 2010;Bougma, et al, 2022;Mesele et al, 2024). In consonance with the significantly (p < 0.05) greater macroaggregates fraction and stability under wet soil condition, greater sorptivity, cumulative infiltration amount, steady state infiltration and saturated hydraulic conductivity were produced under Mm and CMr than Cm.…”
Section: Crop Rotation Effect On Selected Soil Hydro-physical Propertiesmentioning
confidence: 75%
“…Besides contributing to increased SOC, maize roots are also known to produce exudates, which instantaneously bind soil aggregates (Six et al, 2004); thus, maize and legume systems in rotation as in CMr, enhanced macroaggregate stability more than cowpea monoculture (Tables 4 and 5). Some studies reported association of macroaggregates with soil organic carbon content (Six et al, 2000;Curaqueo et al, 2010;Bougma, et al, 2022;Mesele et al, 2024). In consonance with the significantly (p < 0.05) greater macroaggregates fraction and stability under wet soil condition, greater sorptivity, cumulative infiltration amount, steady state infiltration and saturated hydraulic conductivity were produced under Mm and CMr than Cm.…”
Section: Crop Rotation Effect On Selected Soil Hydro-physical Propertiesmentioning
confidence: 75%
“…The relative soil condition of the abandoned anthropogenic grove in the Mole National Park (Tables 1 and 2) seems to exhibit similarity to the Amazonian dark earth or the Terra preta phenomenon with greater carbon and nutrient status than surrounding landscapes (Glaser & Birk, 2012). Apart from the carbon sequestration abilities of these anthropogenic vegetation features in the landscape, their role in soil aggregate stabilization and erosion reduction (Bougma et al., 2022), biodiversity conservation (Fairhead & Leach, 1996) etc., have been reported, making them very useful in the provision of important ecosystem services in the Anthropocene.…”
Section: Discussionmentioning
confidence: 99%
“…Agricultural field plots or farmlands which were under cultivation were selected in as close proximity as possible to the forest island and savanna plots (see Bougma et al [5]). These in Burkina Faso were cotton or cereal-based fields and comprised monocultures of maize in Ghana and maize or intercrop of maize and cassava or legumes in Nigeria.…”
Section: General Research Methodologymentioning
confidence: 99%
“…Early botanists considered forest islands as relics of larger forests destroyed by indiscriminate human activity [2][3][4]. However, more recently, they have been considered 'presumably the direct outcome of human activity' [5]. This notion has been supported by palaeo evidence showing that forest islands are cultivated deliberately on what were originally savanna soils [6].…”
Section: Introduction 1backgroundmentioning
confidence: 99%